Methodology to strengthen the environmental education in athletics - Edelberto Rafael Redondo Reynoso; Faidis Calle Osorio; Alexander Ricardo Coronel Verdecia; Fernando Emilio Valladares Fuente (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The practice of sports is closely related to the environment, especially in the case of athletics. The teaching of this sport has focused on technical aspects such as training for competition, underestimating its potential to strengthen the environmental education. The objective of this research is to propose a methodology to encourage the respect and responsibility towards the environmental elements related to this sport in the practitioners of athletics. For the development of this research, coaches and athletes from the League of Athletics in "La Guajira", Colombia are taken as a sample and for this purpose; methods are applied at an empirical level: scientific observation, survey, interview and documentary review. This work contributes to the integral formation of the trainers of League of Athletics in "La Guajira", and complies with the indicators required by the Olympic Agenda for sustainable development. The results have been satisfactory for the development of sport and its involvement in the interaction of these athletes with the school and the community.